ACCOUNTING IN THE JUNIOR COLLEGES. - Conley, William H. (The Accounting Review, 1939)
During the past decade the American Accounting Association has given attention to the status of accounting and the objectives of different accounting courses in various types of educational institutions of collegiate rank such as the liberal-arts college, the school of engineering, and the school of law. Throughout this same period there has been a rapid development of another type of collegiate institution, the Junior College. In the present discussion of this topic, the nature and the objectives of the junior college, and second, some of the specific problems of organizing accounting in the junior college has been considered. in the higher institutions. A large number of students in junior colleges will terminate their formal education when they complete the two-year unit. This study of accounting in the junior college has been made to point out the nature and the functions of this educational unit, and to discuss some of the problems of one of the popular subjects offered in it, the most important problem being the provision of an introductory course that will meet the needs of a very heterogeneous student body. An effort was also made to show that this problem might be met not by introducing special types of courses but by revising the usual first-year course in such a way that only principles which are necessary for all would be taught.